Study of the Physicochemical Properties, The Anti-Nutrient, Antioxidant and Mineral Composition of Capsicum Annuum Chili Pepper Sold in the Three (3) Main Markets of Korhogo, in the North of Côte d’Ivoire - Michel, Niamke Arthur; Mamadou, Dosso; Adama, Coulibaly; Joseph, Djaman Allico (European Journal of Applied Sciences, 2021)
Capsicum annuum Chili pepper is eaten in Korhogo, in the north of Côte d’Ivoire because of its pungent taste. This species of Chili pepper encounters conservation and distribution problems. In addition, the population does not know its composition or its nutritional value. This study is a valuation of Capsicum annuum chili pepper. The physical properties are: 3.21-3.63cm for length, 6.55cm overall average for circumference, 3.44g overall average for weight, 87.37-88.77% for moisture, 0.82 to 1.02% for ash content. The contents of biochemical elements are: 5.44 on average for the pH, 3.08 meq / 100g on average for titratable acidity, 90.05 to 251.49 mg / 100g for reducing sugars, 2, 92 to 3.55% for total sugars, 0.41 to 0.5% for lipids, 1.46% overall average for protein, 5.53% overall average for fiber, 8.5 to 9.65% for total carbohydrates, 42.89 to 48.72 Kcal / 100g for energy value. Capsicum annuum chili pepper contains 19.58 to 72.91 mg / 100g of vitamin C, 156.15 to 234.21 mg / 100g of polyphenols, 3.28 to 5.89 mg / 100g of flavonoids, and 17.25 to 25.04 mg / 100g of tannins. The contents of anti-nutritional compounds are from 278.67 to 326.33 mg / 100g, 24.61 to 26 mg / 100g respectively for oxalates and phytates.The mineral quantities are 0.137 to 0.180% DM for phosphorus, 0.332 to 0.336% DM for potassium, 0.30 to 0.32% DM for calcium, 0.171 to 0.177% DM for magnesium, 3.14 to 4.54 ppm for copper, 6.58 to 7.83 ppm for iron, 0.45 to 0.84 ppm for manganese, 16.14 to 19.10 ppm for zinc, 6.71 to 14, 08 ppm for sodium.